A Study on the Effectiveness of Online Learning under Complex Dynamic System Theory - Tian, Yuan (Transactions on Social Science, Education and Humanities Research, 2024)
With the acceleration of informatization and the rapid development of Internet information and communication technology, mankind has gradually entered the "Internet +" era. The development of online media has led to continuous innovation in education methods, the speed of knowledge dissemination is increasing day by day, and the breadth of knowledge dissemination is also expanding. As an emerging learning model, online learning is a complete system consisting of teaching and learning, teaching content, learning habits and learning methods, platforms and approaches, and the management of learning resources. A systematic review method was utilized to examine the current state of online learning and make recommendations based on the theory of complex dynamic systems. The study discovered that online learning is complex and systematic, requiring the cooperation of many parties throughout the entire educational system; that it is dynamic and variable, necessitating that teachers update their teaching philosophies and methods for disseminating knowledge; and that its variation of online learning, advising that teachers use stratified teaching to increase students’ autonomy and learning effectiveness.